One‐year sustained glycaemic control and less hypoglycaemia with new insulin glargine 300 U/ml compared with 100 U/ml in people with type 2 diabetes using basal plus meal‐time insulin: the EDITION 1 12‐month randomized trial, including 6‐month extension. Issue 9 (11th May 2015) - Riddle, M. C.; Yki‐Järvinen, H.; Bolli, G. B.; Ziemen, M.; Muehlen‐Bartmer, I.; Cissokho, S.; Home, P. D.
<x xml:space="preserve">Abstract</x> Aims To evaluate the maintenance of efficacy and safety of insulin glargine 300 U/ml (Gla‐300) versus glargine 100 U/ml (Gla‐100) in people with type 2 diabetes mellitus (T2DM) using basal plus meal‐time insulin for 12 months in the EDITION 1 trial. Methods EDITION 1 was a multicentre, randomized, open‐label, two‐arm, phase IIIa study. Participants completing the initial 6‐month treatment period continued to receive Gla‐300 or Gla‐100, as previously randomized, once daily for a further 6‐month open‐label extension phase. Changes in glycated haemoglobin (HbA1c) and fasting plasma glucose concentrations, insulin dose, hypoglycaemic events and body weight were assessed. Results Of 807 participants enrolled in the initial phase, 89% (359/404) assigned to Gla‐300 and 88% (355/403) assigned to Gla‐100 completed 12 months. Glycaemic control was sustained in both groups (mean HbA1c: Gla‐300, 7.24%; Gla‐100, 7.42%), with more sustained HbA1c reduction for Gla‐300 at 12 months: least squares mean difference Gla‐300 vs Gla‐100: HbA1c −0.17 [95% confidence interval (CI) −0.30 to −0.05]%. The mean daily basal insulin dose at 12 months was 1.03 U/kg for Gla‐300 and 0.90 U/kg for Gla‐100. Lower percentages of participants had ≥1 confirmed [≤3.9 mmol/l (≤70 mg/dl)] or severe hypoglycaemic event with Gla‐300 than Gla‐100 at any time of day [24 h; 86 vs 92%; relative risk 0.94 (95% CI 0.89–0.99)] and during the night [54 vs 65%; relative risk 0.84 (95% CI 0.75–0.94)], while the annualized rates of such hypoglycaemic events were similar. No between‐treatment differences in adverse events were apparent. Conclusion During 12 months of treatment of T2DM requiring basal and meal‐time insulin, glycaemic control was better sustained and fewer individuals reported hypoglycaemia with Gla‐300 than with Gla‐100. The mean basal insulin dose was higher with Gla‐300 compared with Gla‐100, but total numbers of hypoglycaemic events and overall tolerability did not differ between treatments.